Kant Yearbook (De Gruyter, 2012)
The Kant Yearbook is an international journal that publishes articles, historical or systematic, on the philosophy of Immanuel Kant. It is the Kant Yearbook's goal to intensify innovative research on Kant on an international scale. Articles are double-blind peer reviewed by an internationally renowned editorial board. Each issue is dedicated to a specific topic announced through a call for papers.